Antiplasmid activity of 1 `-acetoxychavicol acetate from alpinia galanga against multi-drug resistant bacteria - Latha, C.; Shriram, Varsha D.; Jahagirdar, Sheetal S.; Dhakephalkar, Prashant K.; Rojatkar, Supada R. (Journal of Ethnopharmacology, 2009)
Ethnopharmacological relevance: Alpinia galanga (L.) Swartz is traditionally used in the treatment of various ailments across India, China, and Southeast Asian countries. In India it is a reputed drug in indigenous system of medicine and largely used as antibacterial and antiseptic. In southern India the rhizomes has been used as a domestic remedy against bacterial infections. Aim of the study: To identify a potential antiplasmid compound from Alpinia galanga against multi-drug resistant bacteria. Materials and methods: The crude rhizome extract of Alpinia galanga was prepared in acetone. Antibacterial activity was checked by MIC and antiplasmid activity was checked by SIC. The principal compound responsible for the antiplasmid activity, in the crude extract, was identified by bioassay guided fractionation using hexane-acetone. Antibiotic resistance profile of plasmid harboring strains and plasmid cured strains was determined by disc diffusion method. Results: The crude acetone extract of the rhizomes of Alpinia galanga exhibited antiplasmid activity against Salmonella typhi, Escherichia coli and vancomycin resistant Enterococcus faecalis with an efficiency of 92%, 82% and 8% respectively at 400 mu g/ml SIC. The principal compound responsible for the activity was identified as 1'-acetoxychavicol acetate. 1'-Acetoxychavicol acetate demonstrated the ability to cure plasmid encoded antibiotic resistance in various multi-drug resistant bacterial strains of clinical isolates such as Enterococcus faecalis, Salmonella typhi, Pseudomonas aeruginosa, Escherichia coli and Bacillus cereus with curing efficiency of 66%, 75%, 70%, 32% and 6% respectively at SIC of 400-800 mu g/ml. Conclusion: 1'-Acetoxychavicol acetate mediated R-plasmid curing significantly reduced the minimal inhibitory concentration of antibiotics required to inhibit growth of bacteria, thus making the antibiotic treatment more effective. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: 1 `-Acetoxychavicol acetate; Alpinia galanga; Antibiotic resistance; Antiplasmid